KEBIJAKAN FORMULASI PASAL TENTANG WAJIB LAPOR UNDANGUNDANG NOMOR 35 TAHUN 2009 DALAM PERSPEKTIF PERADILAN PIDANA GUNA MEWUJUDKAN PEMBAHARUAN HUKUM PIDANA DI INDONESIA - WIDODO, JOKO (Dinamika Hukum, 2016)
The purpose of this study are: (1) To determine and analyze theformulation formulation of clauses concerning notifiable in Law No. 35 Year2009 on Narcotics in supporting the implementation of the criminal justice systemin order to realize narcotics laws. (2) To know and analyze the policy of criminallaw against narcotic crime through the criminal justice system as criminal lawreform in Indonesia.This type of research used in this thesis is normative research, namely:reviewing laws that are drafted as norms / rules prevailing in society, and to be areference the behavior of every person. The research approach used in this thesisis to use the conceptual approach (conceptual approach), and the approach oflegislation (normative approach). In this case the conceptual or conceptual termsis an understandable thing, in this conceptual framework expressed some conceptsto explain and describe the author of this thesis, namely criminal law policynarcotics criminal justice system. The nature of research is descriptive, ie tomemberikkan fullest picture of criminal law policy narcotic crime throughthe Criminal Justice System in order to reform the law in Indonesia.In the formulation of Law Number 35 Year 2009 on Narcotics found noconsistency imposition of criminal sanctions and the absence of minimum limitkhsusu against the penalty of a prohibited act under the provisions of Act No. 35of 2009 on the Narcotics. The treatment of narcotic crime committed by the policeis in the process of investigation, then Criminal charges against the doersconducted by the Public Prosecutor in accordance with his authority as a publicprosecutor and decided by a judge.Key Word: Formulation Policy Report Article On Mandatory Law Number 35 Of2009 and Criminal Law Revision